2022
DOI: 10.1523/jneurosci.0618-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

c-Kit Receptor Maintains Sensory Axon Innervation of the Skin through Src Family Kinases

Abstract: Peripheral somatosensory neurons innervate the skin and sense the environment. Whereas many studies focus on initial axon outgrowth and pathfinding, how signaling pathways contribute to maintenance of the established axon arbors and terminals within the skin is largely unknown. This question is particularly relevant to the many types of neuropathies that affect mature neuronal arbors. We show that a receptor tyrosine kinase (RTK), c-Kit, contributes to maintenance, but not initial development, of cutaneous axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 65 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…We are particularly interested in the role of receptor tyrosine kinase (RTK) signaling pathways, as these are major regulators of neural development, differentiation, and maintenance. In the case of RBs, the RTKs c-Kit and TrkC have critical roles in neuronal development and axon maintenance (Williams et al 2000; Tuttle et al 2022), but other important RTK pathways in this context have not been identified. Gene Ontology analysis (Ashburner et al 2000) of all three RB subtypes for major RTK pathways revealed expression of genes in the FGF signaling pathway was increased 1.76 fold (number of observed divided by the number of expected genes in this GO category) in RBs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We are particularly interested in the role of receptor tyrosine kinase (RTK) signaling pathways, as these are major regulators of neural development, differentiation, and maintenance. In the case of RBs, the RTKs c-Kit and TrkC have critical roles in neuronal development and axon maintenance (Williams et al 2000; Tuttle et al 2022), but other important RTK pathways in this context have not been identified. Gene Ontology analysis (Ashburner et al 2000) of all three RB subtypes for major RTK pathways revealed expression of genes in the FGF signaling pathway was increased 1.76 fold (number of observed divided by the number of expected genes in this GO category) in RBs.…”
Section: Resultsmentioning
confidence: 99%
“…5A-B). Using a previously established protocol for characterizing the effect of RTK inhibitors on RB axons (Tuttle et al 2022), we treated RB:GFP larvae beginning at 3 dpf with SU5402 for 48 h. This led to a major loss of innervation in the tail skin in a dose dependent manner (Fig. 5C-E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations